2014
DOI: 10.1155/2014/707089
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Hypotonic Treatment for Peritoneal Dissemination from Gastric Cancer Cells: AnIn VivoEvaluation

Abstract: The aim of the present study was to determine the efficacy of a hypotonic treatment for peritoneal dissemination from gastric cancer cells using an in vivo model. We firstly evaluated the toxicity of a peritoneal injection of distilled water (DW) (2 mL for 3 days) in mice. Macroscopic and microscopic examinations revealed that the peritoneal injection of DW did not severely damage the abdominal organs of these mice. MKN45 gastric cancer cells preincubated with NaCl buffer or DW for 20 minutes in vitro were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…When GC cells were incubated with DW, the number of viable cells actually decreased in an exposure time dependent manner. Furthermore, in the in vivo model, 20 min incubation of MKN45 cells with DW, instead of saline, markedly inhibited the formation of peritoneal nodules in nude mice, whereas the microscopic findings did not show any histological damages in the peritoneal mesothelial cells [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When GC cells were incubated with DW, the number of viable cells actually decreased in an exposure time dependent manner. Furthermore, in the in vivo model, 20 min incubation of MKN45 cells with DW, instead of saline, markedly inhibited the formation of peritoneal nodules in nude mice, whereas the microscopic findings did not show any histological damages in the peritoneal mesothelial cells [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the difference in cytocidal effects between cancer and non-cancerous cells, our previous study have already shown that pancreatic cancer cells were more sensitive to hypotonic shock than human lung fibroblast WI38 cells [ 15 ]. Meanwhile, our previous in vivo experiments have also shown that peritoneal injection of DW did not severely damage the peritoneum and abdominal organs of mice, suggesting its safeness in an in vivo use [ 10 ]. Recently, many researchers including ours have reported the expression and role of ion and water channels/transporters for cancer progressions, which also involve in regulating cell volume [ 12 , 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimentally, DW exposure can rapidly increase cancer-cell volume, followed by cell rupture. The cytocidal effect of hypotonic stress on tumor cells has been demonstrated in various malignancies [19,20]. DW has been shown to be able to induce osmotic lysis in colorectal cancer cells [21,22], and more effectively kill cells than cytotoxic chemicals via disassociation with the resistant system of cancer cells.…”
Section: Discussionmentioning
confidence: 99%